APPLICATION METHODS AND SILICON RATES IN TWO WHEAT CULTIVARS CULTIVATE IN NO-TILL SYSTEM - ORIOLI JÚNIOR, Valdeci; ARF, Orivaldo; COSTA, Roberto Savério Souza; BUZETTI, Salatiér (Scientia Agraria, 2008)
Although not to be a nutrient, the silicon can increase the productive potential of some cultures, mainly grasses accumulative of the element, as the wheat. Thus, the objective of this study was to evaluate the development of two wheat cultivars as a function of different silicon rates and two application forms in no-till system. The experimental design was a completely randomized blocks in a factorial scheme 2x6x2 with 24 treatments constituted by combination of wheat cultivars (IAC 24 and IAC 370), silicon rates (zero, 50, 100, 150, 200 and 250 kg ha-1 of Si) and application forms (broadcast and broadcast plus scarification). Was evaluated the growth, the components of yield and the foliar silicon content As a conclusion: IAC 370 cultivar presented higher grain productivity than IAC 24, the silicon rates did not influenced the productivity in both the years, the ways of silicon application did not intervened the productivity of the culture in 2004, but the broadcast plus scarification application propitiated higher productivity to cultivate it IAC 370 in 2005.